Multicystic Peritoneal Inclusion Cyst Presenting as an IncidentalAbdom inal Swelling in a Middle-Aged Wom an: A Rare Case Report - Chavan, Jayant R.; Warpe, Bhushan M; Joshi, Shweta S (Indian Journal of Case Reports, 2026)
Multicystic peritoneal inclusion cyst (PIC), historically designated benign cystic mesothelioma, is an exceptionally rare, benign proliferation of peritoneal mesothelial cells. We report a middle-aged woman in whom a multilocular cystic peritoneal swelling was detected as an incidental finding on abdominal ultrasonography and computed tomography. Serum tumor markers (Cancer Antigen 125, Carcinoembryonic Antigen, and Carbohydrate Antigen 19-9) were within normal limits, and both ovaries and the uterus were visualized separately and appeared normal on imaging. The lesion lacked solid components, septations with vascularity, or any features to suggest malignancy on pre-operative imaging. Diagnostic laparoscopy, converted to open surgery on account of the extent of peritoneal involvement, allowed complete surgical excision. No spillage of cyst contents occurred, and no residual lesion was identified on thorough peritoneal inspection. Histopathological examination confirmed the diagnosis of PIC, demonstrating multiple cystically dilated spaces lined by a single layer of bland mesothelial cells with characteristic hobnail morphology, without atypia, mitotic activity, or stromal invasion. This case illustrates the diagnostic challenge posed by peritoneal cystic lesions, the indispensable role of histopathology in their definitive characterization, and the importance of complete surgical excision given the recognized propensity for local recurrence.